Development and Evaluation of a High-Throughput Single-Nucleotide Polymorphism Array for Large Yellow Croaker (Larimichthys crocea) - Zhou, Tao; Chen, Baohua; Ke, Qiaozhen; Zhao, Ji; Pu, Fei; Wu, Yidi; Chen, Lin; Zhou, Zhixiong; Bai, Yulin; Pan, Ying; Gong, Jie; Zheng, Weiqiang; et al. (Frontiers in Genetics, 2020)
High-density single nucleotide polymorphisms (SNP) genotyping array is an essential tool for genetic analyses of animals and plants. Large yellow croaker (Larimichthys crocea) is one of the most commercially important marine fish species in China. Although plenty of SNPs have been identified in large yellow croaker, no high throughput genotyping array is available. In this study, a high throughput SNP array named NingXin-I with 600 K SNPs was developed and evaluated. A set of 82 large yellow croakers were collected from different locations of China and re-sequenced. A total of 9.34 M SNPs were identified by mapping sequence reads to the large yellow croaker reference genome. About 1.98 M candidate SNPs were selected for further analysis by using criteria such as SNP quality score and conversion performance in the final array. Finally, 579.5 K SNPs evenly distributed across the large yellow croaker genome with an average spacing of 1.19 Kb were proceeded to array production. The performance of NingXin-I array was evaluated in 96 large yellow croaker individuals from five populations, and 83.38% SNPs on the array were polymorphic sites. A further test of NingXin-I array in five closely related species in Sciaenidae identified 26.68% to 56.23% polymorphic SNP rate across species. A phylogenetic tree inferred by using the genotype data generated by NingXin-I confirmed the phylogenetic distance of the species in Sciaenidae. The performance of NingXin-I in large yellow croaker and the other species in Sciaenidae suggested high accuracy and broad application. The NingXin-I array should be valuable for quantitative genetic studies, such as genome-wide association studies, high-density linkage map construction, haplotype analysis, as well as genome-based selection.